Effects of joint immobilization on changes in myofibroblasts and collagen in the rat knee contracture model. Issue 9 (29th March 2017) - Sasabe, Ryo; Sakamoto, Junya; Goto, Kyo; Honda, Yuichiro; Kataoka, Hideki; Nakano, Jiro; Origuchi, Tomoki; Endo, Daisuke; Koji, Takehiko; Okita, Minoru
ABSTRACT: The purpose of this study was to examine the time‐dependent changes in the development of joint capsule fibrosis and in the number of myofibroblasts in the joint capsule after immobilization, using a rat knee contracture model. Both knee joints were fixed in full flexion for 1, 2, and 4 weeks (immobilization group). Untreated rats were bred for each immobilization period (control group). Histological analysis was performed to evaluate changes in the amount and density of collagen in the joint capsule. The changes in type I and III collagen mRNA were examined by in situ hybridization. The number of myofibroblasts in the joint capsule was assessed by immunohistochemical methods. In the immobilization group, the amount of collagen increased within 1 week and the density of collagen increased within 2 weeks, as compared with that in the control group. Type I collagen mRNA‐positive cell numbers in the immobilization group increased at all time points. However, type III collagen mRNA‐positive cell numbers did not increase. Myofibroblasts in the immobilization group significantly increased compared with those in the control group at all time points, and they increased significantly with the period of immobilization. These results suggest that joint capsule fibrosis with overexpression of type I collagen occurs and progresses within 1 week after immobilization, and an increase in myofibroblasts is related to the mechanism of joint capsule fibrosis. The findings suggest the need for a treatment targeting accumulation of type I collagen associated with an increase in myofibroblasts. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1998–2006, 2017.